Mycobacterium ulcerans infection (Buruli ulcer) in French Guiana, South America, 1969–2013: an epidemiological study. Issue 2 (May 2017) - Douine, Maylis; Gozlan, Rodolphe; Nacher, Mathieu; Dufour, Julie; Reynaud, Yann; Elguero, Eric; Combe, Marine; Velvin, Camilla J; Chevillon, Christine; Berlioz-Arthaud, Alain; Labbé, Sylvain; Sainte-Marie, Dominique; et al.
Summary: Background: Mycobacterium ulcerans infection is the third most common mycobacterial disease in the world after tuberculosis and leprosy. To date, transmission pathways from its environmental reservoir to humans are still unknown. In South America, French Guiana has the highest reported number of M ulcerans infections across the continent. This empirical study aimed to characterise the epidemiology of M ulcerans infection in French Guiana between 1969 and 2013. Methods: Data were collected prospectively mainly by two dermatologists at Cayenne Hospital's dermatology department between Jan 1, 1969, and Dec 31, 2013, for age, date of diagnosis, sex, residence, location of the lesion, type of lesion, associated symptoms, and diagnostic method (smear, culture, PCR, or histology) for all confirmed and suspected cases of M ulcerans . We obtained population data from censuses. We calculated mean M ulcerans infection incidences, presented as the number of cases per 100 000 person-years. Findings: 245 patients with M ulcerans infections were reported at Cayenne Hospital's dermatology department during the study period. M ulcerans infection incidence decreased over time, from 6·07 infections per 100 000 person-years (95% CI 4·46–7·67) in 1969–83 to 4·77 infections per 100 000 person-years (3·75–5·79) in 1984–98 and to 3·49 infections per 100 000 person-years (2·83–4·16) in 1999–2013. The proportion of children with infections also declined with time, from 42 (76%) of 55 patients in 1969–83 to 26 (31%) of 84 in 1984–98 and to 22 (21%) of 106 in 1999–2013. Most cases occurred in coastal areas surrounded by marshy savannah (incidence of 21·08 per 100 000 person-years in Sinnamary and 21·18 per 100 000 person-years in Mana). Lesions mainly affected limbs (lower limbs 161 [66%] patients; upper limbs 60 [24%] patients). We diagnosed no bone infections. Interpretation: The decrease of M ulcerans infection incidence and the proportion of children with infections over a 45 year period in this ultra-peripheral French territory might have been mostly driven by improving living conditions, prophylactic recommendations, and access to health care. Funding: Agence Nationale de la Recherche.